Determining the Minimum Infectious Dose of Porcine Epidemic Diarrhea Virus (PEDV) in a Feed Matrix - L. L. Schumacher; J. C. Woodworth; C. R. Stark; C. K. Jones; R. A. Hesse; Rodger G. Main; Jianqiang Zhang; Phillip Charles Gauger; S. S. Dritz; M. D. Tokach (Kansas Agricultural Experiment Station Research Reports, 2015)
Understanding the magnitude of transmissible risk Porcine Epidemic Diarrhea Virus (PEDV)-infected feed imposes and establishing the minimum infectious dose of PEDV in a feed matrix are important components in strengthening virus prevention and control methods. In this study, an experiment was performed involving 30 crossbred, 10-d-old pigs that were used as a bioassay model for the minimum infectious dose of PEDV in feed. The PEDV was first diluted using tissue culture media to form 8 serial 10-fold dilutions. An aliquot of the original stock virus at 5.6 x 105tissue culture infectious dose/ml (TCID50/ml), each serial PEDV dilution, and one virus-negative culture medium were mixed into separate 4.5 kg batches of swine diet to form 10 experimental treatments. The feed was then subsequently evaluated for infectivity using bioassay. Fecal swabs were collected at 0, 2, 4, 6, and 7 d after challenge for PCR testing. At 7 d after challenge, all pigs were necropsied. Cecum contents, ileum and jejunum were collected for PCR, histologic and immunohistochemistry (IHC) evaluation. Overall, the results indicate 5.6 × 101TCID50/g was the minimum PEDV dose in which infection was detected. This feed had a corresponding PCR cycle threshold (Ct) of 37. This is a relatively low dose. To illustrate, using this dose, approximately 1 g of PEDV-infected baby piglet feces could contaminate up to 500 tons of feed. The data confirm that detectable Ct values in feed can result in pig infection. Our results also illustrate that the Ct in feed that was detected as infectious can be above the detection threshold used by some diagnostic laboratories.
Keywords: PEDV; minimum infectious dose; feed